The Influence of Perceived Value on Purchase Intention Through Brand Image at Kambaniru Beach Hotel & Resort, East Sumba - Theresia Silvie Lena Leba; Hananiel M. Gunawan (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
Consumer perception is part of a brand's journey to obtain an image that can be viewed better than before because consumers have evaluated and observed as a whole based on information that has been dug up from various sources. When consumers make a consideration, the variables that need to be evaluated from various existing factors use several types such as in this study using quality of benefits value, monetary value, social status value, information value, preference value, which are expected in this study, will affect the brand image of the object of the researcher's research, namely the Kambaniru Hotel in East Sumba. When the brand image increases, it will eventually give rise to the intention to buy or transact (purchase intention). This study uses a non-probability sampling method that is aimed directly at consumers who have stayed at the Kambaniru Hotel, East Sumba during the period of October 2024. The collection of respondent data is shared online to make it easier for researchers to collect data so that it can be processed later. This study uses SEM (Structural Equation Modeling) analysis with the PLS-SEM application. The results of this study indicate that social status has an influence on brand image and can increase a person or potential consumer to intend to stay at the Kambaniru Hotel when they visit East Sumba